Impact of Islamic psychoeducation in facing the challenges of digital education practices: student and lecturer perceptions - Nurlela, Nurlela; Arifin, Abdul Gafur; Hidayat, Abas (Society for Research and Knowledge Management, 2025)
Educational practices in the digital era offer tremendous opportunities to increase productivity and academic achievement, but dependence on technology brings challenges that lecturers and students must face. A religion-based psychoeducational approach can be a solution to maintain the sustainability of educational practices among lecturers and students to overcome threats in the technological era. This study aims to analyse and predict the strength of Islamic psychoeducation in facing educational challenges in the digital era based on the perceptions of lecturers and students. The research was a quantitative correlational design that used regression data analysis techniques. There were 450 participants from two Islamic-based universities in Indonesia and Malaysia, including 400 students and 50 lecturers. The results showed that integrating Islamic psychoeducational principles in education practice positively impacted students' and lecturers' ability to face challenges in the digital education era. Prediction results indicated that stronger integration of Islamic psychoeducation correlated with greater resilience among lecturers and students in overcoming threats to educational practices in the technological era. Integrating Islamic psychoeducational principles is not only a cognitive strategy but also an authentic experience that helps lecturers and students internalise, feel, and apply religious values directly in facing the challenges of digital education practices. This research provides information that religion is the best source to overcome threat points in the technological era